Connecting - Helen Walker; Carl Vandermeulen; Louise Morgan; Jill Moyer Sunday; Tony Mayo (Journal of the Assembly for Expanded Perspectives on Learning, 2012)
Connecting Helen Walker - Trust, and Gaps Carl Vandermeulen - Proverbs for Poetry Class Louise Morgan - TJ, Whom I Like Very Much Jill Moyer Sunday - History Lesson 101 Tony Mayo - Shawn